The Combination of Probiotic and Calcium Carbonate Decrease Monocyte Count of End-Stage Renal Disease Patient (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Elevated monocyte count is correlated to the decrease of renal function and disease progressivity on end-stage renal disease (ESRD) patients. Probiotic that utilize lactobacillus species is known to play a role in maintaining imunity system balance by inducing the monocyte apoptosis. The combination between probiotic and calcium carbonate could increase probiotic colonization in the gatrointestinal tract. The aim of this study was to analyze the effect of probiotic and calcium carbonate combination toward reduction of monocyte count on ESRD patient at Rumah Sehat Terpadu Dompet Dhuafa Bogor Hospital. This study was true experimental research with randomized pre-post test control group design. Twenty four ESRD patient were randomly enrolled into treatment group (n=12) and control (n=12). The treatment group received probiotic and calcium carbonate, whereas control group received standardized calcium carbonate for 21 days. There was a significant decrease of monocyte (p=0.03) after administration of probiotic and calcium carbonate.